Inclusive Teaching of Integrated Science to Student Teachers with Hearing Impairments in Zambia (Global Journal of Human-Social Science, 2024)
Integrated science is one of the core curriculum subjects for trainee teachers pursuing primary teachers diploma in Zambian colleges of education This study aimed at exploring teaching integrated science to student teachers with Hearing Impairments in an Inclusive environment Five 5 participants from Kitwe College of Education in Zambia who comprised three 3 student teachers with Hearing Impairments and two 2 lecturers took part in the study Some of the findings were that student teachers with Hearing Impairments and Lecturers of science had mixed views on the attitude of student teachers with Hearing Impairments towards learning integrated science but generally felt that students with Hearing Impairments were not adequately attended to during science lessons The study also revealed that lecturers had challenges explaining scientific concepts science terminologies were distorted during sign language interpretation and that student teachers with Hearing Impairments had difficulties comprehending scientific terms The study concluded that adaptive measures for inclusion of student teachers with Hearing Impairments were not adequate and recommended the use of visual aids and assistive technology or multimedia approach during teaching integrated science as well as developing and standardising word-signs for scientific terms to help enhance the learning of integrated science to students with Hearing Impairments
Keywords: hearing impairment; inclusive education; integrated science and teaching